Evaluation of Critical Points for Effective Cryopreservation of Four Different Citrus spp. Germplasm - Damla Ekin Ozkaya; Fernanda Vidigal Duarte Souza; Ergun Kaya (Horticulturae, 2022)
The different pre- and post-treatments are critical in cryopreservation procedures and affect the shoot tip regrowth after freezing. In the present study, the long-term storage of four citrus cultivars [Bodrum Mandarin (Citrus deliciosa Ten.); Klin Mandarin (Citrus nobilis Lauriro); White grapefruit and Red grapefruit (Citrus paradisi L.)] were carried out by droplet vitrification methods, and the critical points for effective cryopreservation of these species were determined. In this study, we investigated the effect of explant size, cold hardening treatments, sucrose concentrations, and media combinations on shoot regrowth after cryopreservation. The highest shoot tip regrowth, ranging from 13.3 to 33.3%, was achieved when they were obtained from 0.3 to 0.7 mm explants excised from cold hardened seedlings at 4 °C for three days that were then precultured in a medium containing 0.25 M of sucrose and treated with PVS2 at 0 °C for 45 min. In addition, it has been determined that a regeneration medium containing boric acid (H3BO3) or ferric ethylenediaminetetraacetate (FeEDDHA) increased the regeneration up to 33.3% after cryopreservation.